Lattice misfit of high refractory ruthenium containing nickel-base superalloys - Neumeier, Steffen; et al. (Advanced Materials Research, 2011)
The influence of Ru, Co, Mo and W on the lattice misfit of eight highly alloyed Re containing single crystal nickel-base superalloys was investigated. High resolution X-ray diffraction (XRD) was used to relate the elemental partitioning behavior and the Vegard coefficients of the elements under investigation to the measured lattice parameter of the gamma and gamma' phase. The residual chemical segregation and especially the coherency stress-induced tetragonal distortion of the gamma matrix lattice in the high Mo containing alloys results in the observation of two different lattice parameters for the gamma matrix phase. This leads to three overlapping, but clearly distinguishable 002 X-ray reflections.
Keywords: Lattice misfit; X-ray diffraction; Ni-base superalloys; Ruthenium